POLICY PAPER: FISCAL POLICY - Fiscal Policy and Redistribution in Ireland - Roantree, Barra (The Economic and Social Review, 2025)
This paper explores the role fiscal policy plays in shaping the distribution of resources through the tax and transfer system in Ireland. It first shows that there has been a shift towards taxes on income and towards expenditure on income transfers as the size of government has increased. This has implications for the amount of redistribution, which appears relatively high compared to other European countries and has risen over the last three decades. However, the tax and transfer system can also shape the distribution of income through the effects it has on the behaviour of individuals, households and firms. Despite an explosion of international research on these effects in recent decades, we have little credible empirical evidence on the magnitude of these effects in Ireland, in large part due to the lack of access for researchers to administrative data.